MDMA-Based Psychotherapy in Treatment-Resistant Post-Traumatic Stress Disorder (PTSD): A Brief Narrative Overview of Current Evidence - Kainat Riaz; Sejal Suneel; Mohammad Hamza Bin Abdul Malik; Tooba Kashif; Irfan Ullah; Abdul Waris; Marco Di Nicola; Marianna Mazza; Gabriele Sani; Giovanni Martinotti; Domenico De Berardis (Diseases, 2023)
Post-traumatic stress disorder (PTSD) is a debilitating mental health disorder that causes significant dysfunction in individuals. Currently, there are many approved pharmacotherapy and psychotherapy treatment options for PTSD, but unfortunately, half of the patients do not respond to traditional therapies. In this article, we review clinical trials and research on 3,4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy in PTSD patients, its pharmacokinetics, and current treatment guidelines for PTSD. Our findings are based on the results of the efficacy of MDMA-assisted psychotherapy from six phase II randomized controlled trials. MDMA-assisted psychotherapy for PTSD has received the “breakthrough therapy” designation from the FDA. MDMA can reduce PTSD symptoms even in treatment-resistant cases by increasing certain neurohormones, i.e., dopamine, serotonin, norepinephrine, and oxytocin. It also modulates activities in the brain regions involved in fear and anxiety. Future research is needed to show whether the advantages outweigh the disadvantages and whether its use can be integrated into available treatment options for PTSD.